Law on environmental protection in tourist villages in the context of sustainable development of the tourism industry: A qualitative case study in Vietnam - Vuong Long, Le; Thanh Phuong, Nguyen; Thanh Khoe, Tran; Thi Thu Van, Tran (Edelweiss Applied Science and Technology, 2024)
After the Covid-19 pandemic, Vietnam’s tourism industry welcomed 1.37 million international visitors. For the whole year 2023, the total number of international visitors will reach 12.6 million, nearly 3.5 times higher than in 2022, exceeding 57% of the original target (8 million) and reaching the adjusted target (12 -13 million views). In Vietnam, which a country which is undergoing economic development, this is a good sign for many workers and businesses, but it can create great pressure on environmental protection in many localities with tourist destinations. For example, as a destination attracting foreign tourists in Hoi A City, Quang Nam Province, Vietnam, the average amount of waste per day is nearly 100 tons; of which single-use plastic waste accounts for 15 - 23% (Thu Huong 2022). In order to prevent and minimize environmental pollution in tourist villages, the Goverment of Vietnam has issued many different documents such as: Decree No. 08/2022/ND-CP orienting no circulation after 2025 and using single-use plastic products and non-biodegradable plastic packaging in tourist areas and destinations; Decision No. 1316/QD-TTg Project to strengthen plastic waste management in Vietnam also points out that by 2025, 100% of tourist resorts and accommodation establishments will not use single-use plastic products and plastic bags which are so hard to decompose. In addition, the Government has also issued a set of criteria guiding environmental protection for tourism establishments and services in tourist areas and destinations, with instructions on minimizing plastic waste...However, around the issue of environmental protection in tourist villages in Vietnam, there are still problems that need to be solved. Through qualitative analysis method, the authors will analyze and propose solutions to remove regulations related to environmental protection mechanisms in tourist villages, aiming at sustainable development of the tourism industry towards a circular economy in the current period.